Determinação do teor de biogás gerado a partir da biodigestão da cama de frango de um aviário do sítio kairós em Guareí-SP - ALMEIDA, Donizeti Rodrigues de; GONCALVES, Gilson Mendes (131, 2024)
Este trabalho tem como objetivo determinar o teor de biogás gerado a partir da biodigestão da cama de frango de um aviário no Sítio Kairós, localizado em Guareí- SP. Utilizando garrafas PET para estimar o volume de biogás e metano, e realizando testes laboratoriais para OD e DBO, buscamos avaliar o potencial energético dos resíduos avícolas. A metodologia envolveu a coleta de amostras de cama de frango, a preparação e inserção dessas amostras em biodigestores feitos com garrafas PET, e a medição do volume de biogás produzido. Testes laboratoriais foram realizados para determinar os níveis de oxigênio dissolvido (OD) e demanda bioquímica de oxigênio (DBO) nas amostras. Os resultados indicam que o aviário pode gerar uma média anual de 115.038 litros de biogás, dos quais aproximadamente 69.023 litros são metano. Esses dados são promissores para a implementação de um sistema de produção de energia renovável, contribuindo para a sustentabilidade e a gestão eficiente de resíduos. Este estudo destaca a importância de explorar fontes alternativas de energia e promover práticas agrícolas sustentáveis, oferecendo uma solução viável para a redução da dependência de combustíveis fósseis e a mitigação dos impactos ambientais.

Bioconstruction emerges as an imperative response to the pressing demands for the implementation of sustainable building practices in the national context. Bioconstruction can be a tool in contributing to the solution of the aforementioned crises, as it not only responds to the need for decent and sustainable housing, but also contributes to adaptation to climate change (NUNES, 2021). This study aims to analyze the evolution and gaps in knowledge in the field of bioconstruction in Brazil and its relationship with sustainability. To this end, a survey of scientific works developed in Brazil in the last 15 years was carried out using the Google Scholar search platform, using the following terms: "bioconstruction", "definition of bioconstruction", "bioconstruction and bioarchitecture", "bioconstruction and permaculture", "bioconstruction and sustainability", "negative points in bioconstruction", "ecological brick", "bioconstruction challenges" and "bioconstruction" "sustainability". Twenty published works on bioconstruction were found between 2010 and 2023. Initially, a survey of works carried out in the last 15 years was proposed. However, during the research, it was found that the availability of relevant data and publications was restricted to the period from 2010 to 2023. This time interval reflects the accessibility of the sources and the relevance of the studies found, being representative of the most significant contributions in the area of ​​interest within the period considered. Most of the works found, 33.3% of them, were published in Scientific Events, followed by undergraduate theses and articles in Scientific Journals. The state of São Paulo had the highest number of publications on the topic (33%), followed by Goiás and Rio Grande do Sul. Regarding the classification of the objectives of the studies, most of them aimed to address "techniques and materials used in bioconstruction", accounting for 26.3% of the publications. The results indicate that further investment is still needed to increase the adoption of bioconstruction in Brazilian construction practices, given that there has been no increase in the number of publications in recent years, despite growing awareness of the need for adaptation due to the various crises facing society.
Keywords: Resíduos orgânicos; Ambiente e Saúde